FPGA-based educational platform for real-time image processing experiments. - Ramirez-Cortes, J.; Martinez-Carballido; Alarcon-Aquino, V.; Gomez-Gil, P.; Emmanuel Morales-Flores (Computer Applications in Engineering Education, 2013)
In this paper, an implementation of an educational platform for real-time linear and morphological image filtering using a FPGA NexysII, Xilinx®, Spartan 3E, is described. The system is connected to a USB port of a personal computer, which in that way form a powerful and low-cost design station for educational purposes. The FPGA-based system is accessed through a MATLAB graphical user interface, which handles the communication setup and data transfer. The system allows the students to perform comparisons between results obtained from MATLAB simulations and FPGA-based real-time processing. Concluding remarks derived from course evaluations and lab reports are presented.
Keywords: education; filtering; hardware; image; processing